Using the Failed Functional Features Hypothesis to Account for the Acquisition of English Locational and Directional Prepositions by Malaysian Chinese Speakers - Chong, Sharon Yee Ling (2007)
This study examines the acquisition of English locational and directional prepositions by Malaysian Chinese speakers in relation to the issues concerning the Failed Functional Features Hypothesis in SLA (Second Language Acquisition) within the Minimalist Program framework. In particular, this study tests the hypothesis of the inaccessibility of a parameterized functional feature [Dir] which is not instantiated in adult learners’ L1 (first language) inventory due to the critical period effect. Chinese is argued to be a language that has no [Dir] feature for its directional expression is controlled by a verb. On the other hand, the English language requires a [Dir] feature which is found in English prepositions to express directionality. Therefore, it is postulated that Malaysian Chinese speakers have persistent difficulty in recognizing the directional reading expressed by English directional and ambiguous prepositions. In contrast, these speakers have no difficulty in recognizing the locational reading expressed by English locational and ambiguous prepositions probably due to the presence of a [Loc] feature in the learners’ L1 inventory. It is argued that after the age of seven (the end of the critical period), L1 Chinese L2 English speakers are not able to acquire the [Dir] feature as the feature is not found in the learners’ L1 inventory and at the same time, the learners are also unable to reset their L1 parameter settings into L2 parameter settings. Two tasks, a Grammaticality Judgment Task (GJT) and a Directionality Judgment Task (DJT) were administered to 100 adult L1 Chinese speakers of L2 English. The former comprises grammatical and ungrammatical items with locational, directional and ambiguous prepositions. The latter consists of items with locational, directional and ambiguous prepositions which convey locational and directional readings. In addition, an Oral Production Task on describing directions was carried out with 12 of the respondents. The findings indicate that while the Chinese speakers were able to acquire the surface structure of the English prepositions, they nevertheless had not acquired the underlying associated features. Such findings are consistent with the view that parameterized uninterpretable functional features are subject to a critical period.